Evolution of the heroic epic of Western Europe during the late Middle Ages (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In the article the features of classical epic that is the product of a collective oral and in writing-individual tradition. Outstanding epics of the late middle Ages were analyzed, such as: «the Song of Roland», «Song of my Cid», «the Song of the nibelungs». Considerable attention is devoted to typological generality of the heroic poems, created by different nations of Europe, which is manifested in the ideological-thematic and artistic levels; due to a number of historical events.
Keywords: Medieval; heroic epic; poem